Reclaiming the loss of the Minangkabau cultural landscape in Negeri Sembilan - Md Jani, Haza Hanurhaza; Mohd. Hussain, Mohd. Ramzi (Elsevier, 2014)
This paper addresses on the issue of the loss of culture and the importance of reclaiming the cultural landscape of the Minangkabau in Negeri Sembilan. Reclaiming the loss of culture is an important initiative in order to protect cultural landscape values or cultural in general. Hence, a study is conducted to provide an understanding towards the importance of reclaiming the cultural landscape in order to protect three main aspects which are the traditions, local practices and sense of identity. It is hoped that this study will contribute to the necessary actions needed to be taken to sustain the cultural landscape.